(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The study of the caracteristics of the Viriatus chieftainship and, in particular, the agreement with the proconsul Fabius Maximus Servilianus in the year 140 B.C., show their importance for the creation of the first form of State in Lusitania. This form of State could not survive because of the stronger power of the roman conquest, but it appears historically as the preciding of the roman province of Lusitania and its territorial and social meaning.